The micromorphological investigation of pollen grains of some important allergenic plants in Kermanshah (West of Iran) - Masoumi, Seyed Mohammad; Fathi, Nashmieh; Hajmoradi, Fatemeh; Baghaeifar, Zahra (Cellular and Molecular Biology, 2019)
Allergenic pollens are found in gardens, fields and green spaces around cities. In Kermanshah, located in the west of Iran, seven allergen pollen samples were collected directly from nature and studied according to the Erdtman acetolysis method by using Light Microscope (LM) and Scanning Electron Microscope (SEM). In this study, atmospheric pollens were also examined by the Durham method. The results showed that the pollen grains were small, medium, and large in terms of size, and Triporate, Pantoporate, Colpate and Tricolporate in terms of aperture. In addition, they were Striate, Perforate, Macroechinate, Microechinate, and Psilate with regard to exine ornamentation; however, the echinate type was more common. In general, Prolate to a spherical shape, medium-sized, perforate, and echinate pollen characteristics are popular in the important allergenic plants. Therefore, due to the human’s manipulations in nature and also the extensive size of gardens and fields, there are many types of weeds in Kermanshah Province which are significant in terms of being allergenic.